The hypolipidemic activity of ethanolic extract of seed kernel of Caesalpinia bonducella fleming on serum lipids and atherogenesis in albino rats fed with high fat diet - Sarma, Gayatri; Das, Swarnamoni (International Journal of Basic & Clinical Pharmacology, 2018)
Background: An increase in the incidence and prevalence of hyperlipidemia in India has led to an increased demand for drugs with a lipid lowering potential. Thus, the present study was undertaken to evaluate the hypolipidemic activity of ethanolic extract of seed kernel of Caesalpinia bonducella Fleming (EESKCB) in albino rats fed with high fat diet. Methods: The extract was daily administered to healthy adult albino rats of either sex, fed with high fat diet for a period of 60 days. At the end of 60 days, i.e. on the 61st day, serum cholesterol, serum triglyceride, serum low density lipoprotein cholesterol, serum high density lipoprotein cholesterol, atherogenic index, the body weights of the rats and the serum levels of malondialdehyde (MDA) and catalase were estimated. Phytochemical analysis of the plant extract was also carried out. For statistical analysis, the methods employed were One-way ANOVA, Dunnett’s multiple comparison test and Student’s ‘t’ test (Paired). Values of p < 0.05 were considered significant. Results: The test drug brought about significant (p<0.05) decrease in the raised levels of all the lipid parameters except the High density lipoprotein cholesterol. There was also a significant (p<0.05) increase in the serum levels of catalase and a significant (p<0.05) reduction in the serum levels of MDA in the test drug treated group. The test drug also significantly (p<0.05) inhibited the rise in body weights of the rats. Conclusions: From this study, it can be said that the seed kernel of Caesalpinia bonducella Fleming has significant hypolipidemic activity.